The BPJS Patient Medical Services on Doctor Work Satisfaction at Public Hospital Royal Prima Medan - Ali Napiah Nasution; Daniel Prem Raj Pandid; Chrismis Novalinda Ginting (Jurnal Scientia, 2024)
A health worker who has an important role in the service at a hospital is a doctor. At RSU Royal Prima Medan, the medical services received by doctors are considered insufficient which causes dissatisfaction with doctors at work. Based on the results of the performance evaluation of doctors in December 2017, the percentage decreased from 80% to 76.3%. This study was to analyze perceptions about the distribution of the amount of medical services, the timeliness of providing medical services, the compatibility of medical services with performance, the distribution system, transparency, work environment, co-worker relations, and promotion opportunities on doctor's job satisfaction. This study uses a type of survey. All 48 specialist doctors at RSU Royal Prima Medan are the population as well as the sample in this study. Analysis was performed on bivariate data using chi-square and then for multivariate data using logistic regression test α = 0.05. The doctor's satisfaction level is influenced by the distribution system and promotion opportunities. The opportunity for promotion has a regression coefficient (B) of 2,887 so that it is the main factor influencing the level of doctor satisfaction.